2007
DOI: 10.2740/jisdh.18.216
|View full text |Cite
|
Sign up to set email alerts
|

Effects of retort pouched rice containing pre-germinated brown rice on daily nutrition and physical status in healthy subjects

Abstract: We examined the daily nutrition, the physical status and biochemical analysis of the blood effect of retort pouched rice containing pre germinated brown rice on healthy female university students The subjects daily ingested 400g of retort pouched rice containing pre germinated brown rice polished rice: pre germinated brown rice =

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Another clinical study on healthy female university students revealed that ingestion of brown rice as a staple food for 10 weeks improved general health and prevented hyperlipidaemia, thus protecting against CVD [ 101 ]. Several pre-clinical studies have also reported anti-hypertensive effects of germinated brown rice in spontaneously hypertensive rats [ 102 , 103 ].…”
Section: Nutrigenomic Implications Of Brown Ricementioning
confidence: 99%
“…Another clinical study on healthy female university students revealed that ingestion of brown rice as a staple food for 10 weeks improved general health and prevented hyperlipidaemia, thus protecting against CVD [ 101 ]. Several pre-clinical studies have also reported anti-hypertensive effects of germinated brown rice in spontaneously hypertensive rats [ 102 , 103 ].…”
Section: Nutrigenomic Implications Of Brown Ricementioning
confidence: 99%